Optimalisasi Kinerja Organisasi melalui Penerapan Sistem Informasi Manajemen Berbasis Teknologi Terintegrasi dan Tata Kelola Adaptif - Salim Maula Amrullah; Abdur Rosyid Amrullah; Andrianto; Danang Ardiansyah; Rivaldi Pratama Kurnia (Jurnal Riset Multidisiplin Edukasi, 2025)
The implementation of Management Information Systems (MIS) has become a crucial strategy for enhancing organizational performance in the era of digital transformation. This study aims to analyze and synthesize research findings related to the implementation of MIS across various organizational sectors in order to identify its impacts, benefits, and key success factors. The method employed is a systematic literature review of ten nationally accredited scholarly articles published between 2019 and 2024. The research stages include definin\g inclusion and exclusion criteria, searching national journal databases, content analysis, and thematic synthesis. The results indicate that the implementation of integrated, technology-based MIS significantly contributes to improved operational efficiency, decision-making quality, process transparency, and overall organizational performance. The success of MIS implementation is influenced by the alignment of the system with organizational needs, effective information technology governance, and the readiness of human resources. These findings are expected to serve as a reference for organizations in designing and implementing MIS in an effective and adaptive manner.